The inverse surfaces of tangent developable of a timelike curve in minkowski space E31 - Aydin, M. Evren; Ergüt, Mahmut (My University, 2013)
In this paper, we study inverse surfaces in Minkowski space E 31. We obtain various relations between these surfaces. Also we give some necessary and sufficient conditions so that the the inverse surface of tangent developable of a timelike curve is flat or minimal in E 31 . © 2013 Academic Publications, Ltd.
Keywords: Inverse surface; Tangent developable surface; Timelike curve